Gabrielle Vassal (1880–1959): collecting specimens in Indochina for the British Museum (Natural History), 1900–1915. Issue 1 (April 2020) - Gulliver, Katrina
Abstract : Gabrielle Maud Vassal and her husband Joseph Marguerite Jean-Baptiste Vassal, a physician in the French Colonial Service, supplied bird and mammal specimens from French Indochina and later from French colonies in Africa (Gabon, Congo) to the British Museum (Natural History) between 1900 and 1930. Gabrielle Vassal was a keen naturalist and an engaging correspondent, and many of her letters are preserved. The couple moved to Indochina (Vietnam) in 1904, and this paper focuses on her time there prior to the First World War, and how she built a relationship, both professional and personal, with staff of the Museum. Her main correspondents at that time were William Robert Ogilvie-Grant and Michael Rogers Oldfield Thomas. As a woman collector, she was unusual – especially for operating in French territory and sending specimens to a British museum. Her specimens included several newly-discovered species, and a number were named after her, including Nomascus gabriellae, and her husband. She became a successful photographer, public speaker and author, recounting her travels and experiences.